Intravenous Lacosamide in Seizure Clusters: Dose and Efficacy. Issue 3 (May 2021) - Eilam, Anda; Khmeliov, Nadejda; Penker, Delit; Gilad, Ronit
Abstract : Purpose: The objective of our study was to evaluate the relationship between the loading dose and efficacy of lacosamide (LCM), when used in seizure clusters (SCs). Methods: A cohort of patients with SC treated with intravenous (IV)-LCM between September 2017 and September 2019 was retrospectively examined. Demographic data, type of seizure emergency, etiology, response rate, previous oral antiepileptic drugs used, total LCM loading dose, and side effects were reviewed. Results: Thirty-nine cases of epileptic emergencies treated with IV LCM were collected. The mean age was 59.25 years (18–88 years), and the median loading dose was 136.5 mg (100–300 mg) with a response rate in the whole population of 29.2%. Nine patients received a loading dose of 200 to 300 mg, and their response rate was 89%. Common side effects (drowsiness and dizziness) were mild. No electrocardiogram changes or other cardiovascular side effects, or unexpected side effects were seen. Conclusions: In adults with SC, a loading dose of IV LCM of 200 mg or more achieved 89% response rate in this cohort. Loading doses of less than 300 mg caused mild side effects only.